2020
DOI: 10.1007/s00280-019-04028-5
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of exposure-driven myelotoxicity of continuous infusion 5-fluorouracil by a semi-physiological pharmacokinetic–pharmacodynamic model in gastrointestinal cancer patients

Abstract: Purpose To describe 5-fluorouracil (5FU) pharmacokinetics, myelotoxicity and respective covariates using a simultaneous nonlinear mixed effect modelling approach. Methods Thirty patients with gastrointestinal cancer received 5FU 650 or 1000 mg/m 2 /day as 5-day continuous venous infusion (14 of whom also received cisplatin 20 mg/m 2 /day). 5FU and 5-fluoro-5,6-dihydrouracil (5FUH2) plasma concentrations were described by a pharmacokinetic model using NONMEM. Absolute leukocyte counts were described by a semime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…In general, the identified covariates on 5FU PK vary considerably. A similar influence of BSA was identified in two other published population PK models as well, 41 , 42 whereas other models revealed significant effects of sex, 36 , 43 age, 44 or body weight. 45 When applying the initial model on the new dataset, all SMI measures were positively associated with 5FU clearance when adding them as covariates and significantly improved the model fit.…”
Section: Discussionsupporting
confidence: 79%
“…In general, the identified covariates on 5FU PK vary considerably. A similar influence of BSA was identified in two other published population PK models as well, 41 , 42 whereas other models revealed significant effects of sex, 36 , 43 age, 44 or body weight. 45 When applying the initial model on the new dataset, all SMI measures were positively associated with 5FU clearance when adding them as covariates and significantly improved the model fit.…”
Section: Discussionsupporting
confidence: 79%
“… 42 ). These findings collectively indicates that negative effects of 5-FU on embryonic development is closely related to its dosage, which in turn suggests that it is crucial to apply an optimal dosage that has expected anticancer activity but does not induce significant developmental defects (Refs 43 , 44 ). In this context, the mouse embryonic stem cell test seemed extremely useful to assess the developmental toxicities and determine the optimal dosage of 5-FU (Ref.…”
Section: Adverse Effects Of 5-fu On Female Reproductionmentioning
confidence: 83%
“…5-FU chemotherapy is immunosuppressive and a linear relationship between 5-FU plasma concentration and decreased leukocyte count was observed [ 109 ]. A recent study indicated 70% of CRC patients treated with 5-FU according to the Mayo schedule experienced ≥grade 1 hematological toxicities (neutropenia and/or leukopenia) [ 40 ].…”
Section: 5-fu Modulates the Anti-tumor Immune Responsementioning
confidence: 99%